DEVELOPMENT OF SOCIALLY ORIENTED BUSINESS: INTERNATIONAL EXPERIENCE AND UKRAINE - Зелінська, Галина Олексіївна; Андрусів, Уляна Ярославівна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2024)
The article is devoted to issues of formation and development of socially oriented business in Ukraine. To reveal the topic of the research, the experience of the functioning of social business abroad is used and its adaptation in the real conditions of our country is proposed. In particular, issues related to the corporate social responsibility of business to the state and consumers of its services are revealed. The state, as the general subject of social management, is interested in the development of social entrepreneurship, innovations, resorting to competent business management. It allows business not only to survive, but also to develop in an objectively existing competitive environment. It was found that the development of socially oriented business abroad has come a long way and its management is characterized by the peculiarities of culture, mentality, and the region where it operates. &nbspAnalyzing different models of corporate governance abroad, we can note that the role of the state is different: from full intervention to moderate and indirect. In Ukraine, only the initial stage of social business development is observed. Improvement and development of new legislative support for the mechanism of organizational and economic measures regarding the effective use of social entrepreneurship at different levels of management are needed. &nbspIt was determined that for the development of socially oriented business in Ukraine, it is worth using the best examples and models of world management, adapting them to our conditions, taking into account the peculiarities of the development of the territory, its infrastructure support and the mentality of the population. The article uses general research methods, in particular general scientific methods, to reveal the content of the research; abstract-logical - to substantiate conclusions; comparison - for the analysis of information, etc., of the development of social business in the industrially developed countries of America, Europe and Asia. Among the traditional methods of revealing the content of the article, we highlight the literary method of research - the study of Internet sources, laws, monographs, articles and other publications, etc. Transformation of business structures in Ukraine on an innovative basis is a necessary condition for their development. Ensuring such a process will allow creating prerequisites for the country’s socio-economic growth in the long term by increasing the intellectual potential of society, providing the labor market with human resources on the one hand and on the other - a difficult task due to the powerful influence of a number of subjective factors, caused in particular by the unpreparedness of senior management personnel in making flexible decisions in war conditions, the underdevelopment of social infrastructure, the lack of transparent relations between the state and business structures, public and local communities.